(untitled) (Global Journal of Management and Business Research, 2015)
Small and specialized companies are finding it very difficult to be competitive and survive in phenomena such as globalization and the expansion of large supermarket chains. They must face the evolution of the consumer, taking into account their new preferences and lifestyle. It is important to study the segment of supermarkets and specialty stores as well as knowing the projection of the main consumers in the coming years.